Sekuritisasi Isu Maritim: Koordinasi Nasional dan Kerangka Kerja Sama Maritim Regional di Asia Tenggara - Perwita, Anak Agung Banyu (UI Scholars Hub, 2004)
This article discusses the significance of Malacca Straits as one of the pivotal sea lines in the world. It argues that the security of Malacca Straits involves the nexus of external and internal maritime security and therefore it should be assessed by dual approach. This article emphasize the maritime security problems in the Malacca Straits and concludes by advocating a more comprehensive maritime security framework—particularly to Indonesia, ASEAN, and other non-regional actors—in order to bring new approaches to the maritime security problem in the Malacca Straits.